Fortificaties in Hollantsch Brasil (Bulletin KNOB, 1991)
To study the past, military buildings are as good a historic source as churches. Both types of architecture have been engineered a more permanent material than most of the contemporary houses. Thus to the colonial-historian fortifications possess a wealth of material on the history of military science, the history of architecture, on style and social economic history.After the Dutch invaded Pernambuco in february 1630 they adapted the Portuguese fortifications and started to build new forts to consolidate the acquired possessions. Available plans of these forts demonstrate well thoughtout schemes. As authority on the field of the highly influential Italian theories on fortifications the Dutch fortress engineer Simon Stevin adapted these theories to Dutch circumstances and needs. In the colonized regions fortress engineers from this School of Stevin were put to work by the Dutch West-lndian Company. Stones and suitable materials were imported from the Netherlands.No specific manuals have come down to us on form, strategic projection or materials but there exists a writing of Simon Stevin from 1594 with designs of the early Dutch-Brazilian fortifications, which can be reduced after the material as mentioned in this manual. Another source is the diary of the German mercenary Ambrosius Richshoffer, who signed on in Amsterdam in 1629.The most spectacular example of Dutch forts in Brasil was the pentagon In face of the devil. After a thorough restoration the fort at present houses the townmuseum of Recife with a varied selection of documents on the Dutch period (1630-1654).Fort Triangle was built on a shallow between the island António Vaz, the isthmus and the continent and played an important role during the siege of Recife in 1645.Fort De Bruyn was built in 1630 on the site of a small Portuguese entrenchment to the east of Recife. This square fort has been restored drastically by the Portuguese.Fort Orange (1633), situated on the island of Itamaraca, was designed and carried out by Pieter van Bueren, Andreas Drewisch and perhaps by Cristóvao Alvares. The square plan has been laid out in conformity with the classic Italian notion of a fort, which still was valid in the 17th century. This fort stands out by a remarkabie doublé entrance. This system after Caernavon (1283) has been introduced in Europe by the knights of the Cross.In 1645 the forts on Itamaraca were strengthened thoroughly. Fort Ernestus, built around a Franciscan monastery, this way was converted into a real fort directed against attacks from the interior.Thus in 1654 there were 39 forts and entrenchments along the Dutch-Brazilian coastal strip. This implies the importance of the Brazilian colony. The downfall of the region to the Dutch West-lndian Company is caused by the fact that military spending was too high with respect to the desired income.The form of the forts built by the Dutch outside of Europe often was pentagonal. In the ecclesiastical, military and civil architecture from the fifteenth and sixteenth century the pentagon carried a mystic meaning and was a symbol of the imperfection of man compared to God, who was symbolized with the numbers 7 and 8.In the 17th century the vision on the function of the fort was much more pragmatic and the number of bastions reduced from five to four. Still, in the habit of name-giving, calling forts after important places, beloved persons or dignitaries an element of symbolism remained connected with forts and fortifications.